ANALISIS KESESUAIAN ANTARA IMPLEMENTASI KEBIJAKAN AKUNTANSI ASET TETAP DENGAN STANDAR AKUNTANSI PEMERINTAH ASET TETAP BERBASIS AKRUAL PP 71 TAHUN 2010 (Studi Kasus Pada Kebijakan Akuntansi Pemerintah Kota Samarinda) - Ismadi, - Bambang (EKONOMIA, 2019)
BAMBANG ISMADI, 2017, Faculty of Economics, University of August 17 1945 Samarinda, East Kalimantan, Intermediate Analysis of the Implementation of Fixed Asset Accounting Policies with Accrual Based Government Accounting Standards PP 71 of 2010 (Case Study of Samarinda City Government Accounting Policies) under the guidance of Mr. Robin Jonathan and Mrs. Elfreda Aplonia Lau.The purpose of this research is to find out and analyze the implementation of Accrual Based Local Government Accounting Policies that have been running starting in Fiscal Year 2015 as an evaluation material for the application of PP 71 of 2010 concerning Accrual-Based Government Accounting Standards, especially fixed assets. The problem in this research is whether there is a difference between the implementation of the Fixed Asset Accounting Policy and the Government Accounting Standards for Fixed Assets Based on Accrual PP 71 of 2010 on the Government of Samarinda City. Is the difference detected by the External Examiner in this case the BPK? , and is there an Action Plan or Action Plan to resolve these differences?The theoretical basis of this study uses PP 71 of 2010 concerning Government Accounting Standards. The hypothesis in this study is that there is a difference between the implementation of Fixed Asset Accounting Policies and Government Accounting Standards for Fixed Assets Based on Accruals PP 71 of 2010 on Samarinda City Government, differences were not detected by External Examiners, there was an action plan to resolve these differences. Data collection techniques are carried out by means of field research and library research. The data used to find out and analyze the suitability between the implementation of fixed asset accounting policies and Government Accounting Standards based on Accruals based on PP 71 of 2010 are the 2015 Samarinda City Financial Statements, Samarinda City Government Accounting Policies, Samarinda City Government Accounting Systems and Procedures, Flowcharts / System Requirements for recording in SIMDA-Finance and SIMDA-BMD, and LHP BPK for the 2015 Samarinda City Government Financial Report. The analytical tool used is the comparative method and using the observation method.The results of the study were 13 differences in implementation, 8 differences were found from observations of the implementation of simda applications, and 5 differences were found from interviews with accounting fields, for 13 differences were juxtaposed with LHP BPK, there were 4 differences in implementation found by CPC, and 4 differences found by the CPC, 3 differences have been included in the action plan document.